Effects of coconut oil (Cocos nucifera) and sesame oils (Sesamum indicum L.) on rapeseed powder induced changes of cardio-hepatic enzymes in Wistar rats. - Rahman, Hafizur; Rahman, Shaikh Shahinur (Progress in Nutrition, 2018)
Purpose: Rapeseed oil contains high percentage of erucic acid which causes cardio-hepatic toxicity. Methods: In this study, different doses of sesame oil (SO) and coconut oil (CO) were mixed with constant dose of rapeseed oil and fed to Wistar rats for 6 weeks. After the experimental period, abdomen aortic blood was collected and serum enzymes level such as CK-MB, SGOT and SGPT were measured. Results: Rapeseed oil not only increased SGPT enzyme level over control diet but also elevated CK-MB and SGOT significantly. Whereas, sesame oil and coconut oil showed protective effect against rapeseed oil induced cardio-hepatic enzymes. Moreover, higher doses of both oils represented better effect against rapeseed oil toxicity. Although CO and SO significantly decreased serum CK-MB, SGOT and SGPT activities, coconut oil had greater effect on cardiac enzymes like CK-MB while sesame oil were more significant for SGPT and SGOT. Conclusion: Therefore, the ameliorating effects of sesame oil and coconut oil trimmed down the toxic effects of rapeseed oil in rats.